The effect of training and work motivation on employee performance at the Regional Inspectorate of Southeast Sulawesi Province - Permatasari, Intan; Abbas, Bakhtiar; Putera, Asrip (Journal of Business Management and Economic Development, 2024)
Human resources (HR) is a crucial factor in determining the success of the organization. The Regional Inspectorate of Southeast Sulawesi Province has an important role in ensuring the implementation of government policies and programs goes according to plan, but faces challenges in improving employee performance. There is a knowledge gap regarding the simultaneous influence of training and work motivation on employee performance in the context of local government. This study used multiple linear regression method to analyze data collected through questionnaires from 45 employees. The results show that job training has a positive and significant effect on employee performance with a regression coefficient of 0.840, while job motivation has a regression coefficient of 0.956, also a positive and significant effect. In addition, the interaction between training and work motivation showed a greater effect, indicating that the combination of these two factors is very effective in improving performance. The study also found that although overall these two factors had a positive influence, there were some employees who did not show an improvement in performance, indicating that there are other factors that may affect employee performance. The implication of this study is the importance of integrating comprehensive training programs and work motivation enhancement strategies to improve overall employee performance.